Study of the association of cord serum albumin with neonatal hyperbilirubinemia among neonates with neonatal hyperbilirubinemia among neonates in a teritary care hospital - Roach, Vipin; Kumar, Pancham; Sood, Arvind; ., Sachin (International Journal of Contemporary Pediatrics, 2022)
Background: Neonatal hyperbilirubinemia (NH) is the most prevalent aberrant physical finding in the first week of life, affecting about 60% of term and 80% of preterm neonates. Hyperbilirubinemia is more common in preterm infants due to a variety of causes, although it can also occur in healthy term infants. The liver produces albumin, which aids in the transport of unconjugated bilirubin. Hyperbilirubinemia can be predicted early, allowing newborns and mothers to be discharged sooner and stay in the hospital for less time. Objective were to study cord albumin levels, to study the proportion of newborn requiring intervention for neonatal jaundice (phototherapy or exchange transfusion) based on different levels of cord blood albumin (CBA) level at birth and thereby defining the critical cord blood albumins values with respect to significant neonatal jaundice. Method: The 200 cases who filled the inclusion and exclusion criteria were included into the study for predictive value of CBA for NH. Then the data was analyzed using epi info and descriptive and inferential statistics were used. Result: In the present study, term group had 49 males and 45 females, while preterm group had 62 males and 47 females respectively. There was no significant association between gender and NNHB in either of the two groups (0.75 in term; 0.09 in preterm). There was also no association found between NH and the mode of delivery, in both term and preterm neonates with p=0.88 in term group and 0.84 in preterm group respectively. In our study, in the term group, only 1 (100%) with birth weight less than 2.5 kg developed significant NH. Only 33 (35.5%) out of 93 newborns with birth weight more than 2.5 kg developed NH. With p=0.01, there was significant association between birth weight and significant NH. Among preterm newborns, there was a significant association between birth weight and development of significant NH (p=0.0001). Conclusions: In present study findings showed that CBA level can be used as a predictor of NH in a term as well as preterm newborn soon after birth. As cord blood is easily available in an institutional delivery and albumin estimation also easily done which can help in recognizing risk group (low CBA) and strict vigilance should be followed.